2021
DOI: 10.3390/vaccines9101084
|View full text |Cite|
|
Sign up to set email alerts
|

Immunogenicity of Recombinant-Deficient Lactobacillus casei with Complementary Plasmid Expressing Alanine Racemase Gene and Core Neutralizing Epitope Antigen against Porcine Epidemic Diarrhea Virus

Abstract: Porcine epidemic diarrhea (PED), which is caused by the porcine epidemic diarrhea virus (PEDV), has occurred worldwide and poses a serious threat to the pig industry. Intestine is the main function site of PEDV; therefore, it is important to develop an oral mucosal immunity vaccine against this virus infection. Most traditional plasmid delivery vectors use antibiotic genes as a selective marker, easily leading to antibiotic accumulation and gene contamination. In this study, to explore whether the alanine race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Li et al applied alanine racemase-deficient L. casei W56 as the host strain and a complementary plasmid as a vector to express the neutralizing antigen COE of PEDV. After the oral immunization of mice, both SIgA and IgG levels increased significantly (Li et al 2021 ). In this study, the protective antigen S1 gene of PEDV was inserted into the genome of the strain △ Alr HLJ-27 to construct the mutant strain S1/ △ Alr HLJ-27 .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al applied alanine racemase-deficient L. casei W56 as the host strain and a complementary plasmid as a vector to express the neutralizing antigen COE of PEDV. After the oral immunization of mice, both SIgA and IgG levels increased significantly (Li et al 2021 ). In this study, the protective antigen S1 gene of PEDV was inserted into the genome of the strain △ Alr HLJ-27 to construct the mutant strain S1/ △ Alr HLJ-27 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that utilizing LAB to develop an oral vaccine to deliver foreign antigens can help induce the production of IgA antibodies in animals. Li et al used auxotrophic L. casei and its complementary plasmid to express the non-toxic antigen of Porcine Epidemic Diarrhea Virus (PEDV), and the results showed that it could stimulate the production of sIgA and IgG in mice [ 35 ]. Therefore, we endeavored to test the immunogenicity of pPG-E-α-β2-ε-β1/ L. crispatus N-11 in chickens, immunized orally using ELISA and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report on the use of lactic acid bacteria as a carrier for vaccine antigens, many studies have been published ( 12 ). Attempts have been made to use recombinant LAB strains in immunoprophylaxis against gastrointestinal pathogens ( Salmonella , Helicobacter , Yersinia ), bacteria that cause respiratory infections ( Streptococcus pneumoniae ) ( 5 ), as well as against numerous viruses such as SARS-CoV-2 ( 13 ), Human Papilloma Virus ( 14 ), rotavirus ( 15 ), Porcine Epidemic Diarrhea Virus ( 16 , 17 ), and subgroup J Avian Leukosis Virus ( 18 ). Various strategies have been developed to efficiently express genes encoding heterologous antigens in LAB strains, mainly of the genera Lactococcus and Lactobacillus .…”
Section: Introductionmentioning
confidence: 99%